PENGARUH KEMUDAHAN INTERNET BANKING TERHADAP KEPUASAN NASABAH PT BANK CENTRAL ASIA KANTOR CABANG UTAMA SURYOPRANOTO - Darmeinis, Darmeinis; Yenny, Yenny (Lembaga Pengembangan Kinerja Dosen, 2022)
The activity of saving money today is the main thing for planning the future. Banks as one of the most trusted financial institutions have information technology innovations so that financial transactions become more effective and efficient. Banking technology, called internet banking, has features that provide convenience for customers in transactions that have an impact on customer satisfaction in their use. This paper will analyze the convenience of internet banking on customer satisfaction an PT Bank Central Asia’s main branch office Suryopranoto using a simple regression method, as many as 30 respondents were surveyed through a questionnaire to test the research model. The results of the study indicate that there is a weak and positive relationship between the convenience of internet banking and customer satisfactions because most of the customer satisfaction is influenced by other factors.